ECONOMIC PERFORMANCE OF THE FOOD INDUSTRY AND ITS CORRELATION WITH FOOD AFFORDABILITY IN INDONESIA - Poppy S. Nurisnaeny; Djoko Andoko; Saparuddin Saparuddin (Adisam Publisher, 2025)
This study aims to examine the economic performance of the food industry in Indonesia and identify its correlation with the level of food affordability by the community. Using a literature review method, this study collects and analyzes various academic sources, policy reports, and statistical data from national and international institutions to describe the dynamics of the food sector in the context of economic growth, production efficiency, and food distribution. The results of the study indicate that the food industry has a strategic role in the national economy, both as a driver of the agribusiness sector and as a determinant of social stability through the availability and affordability of food. However, structural challenges such as distribution inequality, dependence on imported raw materials, and fluctuations in food commodity prices are still major obstacles in realizing equitable food affordability. A positive correlation was found between the growth of the food industry's performance and increased food affordability, although the impact was not evenly distributed throughout Indonesia. Therefore, strengthening national food policies and increasing supply chain efficiency are key to encouraging food security and justice in the future.